ANALISIS PENGARUH COMPANY EFFICIENCY, LIQUIDITY, DAN LEVERAGE TERHADAP PROFITABILITY - Feradella, Cynthia; Tjakrawala, Kurniawan (Jurnal Paradigma Akuntansi, 2024)
This study aims to obtain an empirical evidences regarding the effect of company efficiency, liquidity, and leverage on profitability in property and real estate companies listed on the Indonesia Stock Exchange during the 2016-2020 period. The sample of this research is 41 samples of property and real estate companies with a minimum number determined through the Slovin formula and selected using the purposive sampling method. The data in this study are secondary data obtained from financial reports and annual reports. The data were processed using the SPSS 25 program. The results of this study shows that company efficiency has a significant positive effect on profitability, while liquidity and leverage have a significant negative effect on profitability.